O uso estratégico das redes sociais para impulsionar a visibilidade de clínicas odontológicas em Codó - MA - Silva, Ana Carolina Lima (2024)
With the exponential advancement of the technological era, there is a clear need for organizations to implement new practices to ensure their notoriety and permanence in the market. In this approach, a new figure emerges, social networks, which act as a means of dissemination, information, credibility and maintain closer contact with customers. Therefore, there was a need for research that would understand what motivates dental clinics in Codo to use these digital mechanisms to boost their visibility. In view of this, to answer the research problem, the general objective was: Identify the results obtained by dental clinics when using social networks as a strategic tool to leverage their notoriety in the Codoense market. Furthermore, specifically, the objective was to: analyze the relevance of social networks as a mechanism for boosting market visibility in dental clinics; identify the main visibility strategies adopted by dental clinics, to stimulate their visibility through social networks and verify the effects of public engagement through social networks on the results of dental clinics. Finally, a quantitative approach was used, through exploratory research. The data were obtained from the application of a questionnaire, which was based on the Likert scale, applied specifically in dental clinics. Therefore, it was made sure that dental clinics realized that a large part of customers and potential customers use some social network in their daily lives, and that normally these digital vehicles tend to influence the purchasing power of their users, considering the agility of access to information and credibility, therefore, clinics see considerable potential in these platforms in terms of leveraging the company's notoriety in the marketing context.